Transcranial Direct Current Stimulation for tinnitus: towards an improved understanding to facilitate clinical translation - Labree, Bas (2024)
Tinnitus is the perception of sound in the absence of an external source. It is a highly prevalent condition, comorbid with depression, anxiety, insomnia and reduced quality of life. There is no cure and existing management strategies tend to address the impact of tinnitus, rather than the percept itself. Transcranial Direct Current Stimulation (tDCS) is a potential treatment for tinnitus. TDCS works via a low-intensity direct current delivered through electrodes on the head. It is postulated to modulate tinnitus-associated neural activity in the affected region(s) of the brain, thereby reducing the severity of tinnitus symptoms. TDCS is used for various health conditions, but no optimal set of stimulation parameters exists for the treatment of tinnitus. This is a major hurdle to future large-scale clinical trials to assess its efficacy and safety.